The Liaonan/Wanfu metamorphic core complexes in the Liaodong Peninsula: Two stages of exhumation and constraints on the destruction of the North China Craton. Issue 5 (1st October 2013) - Liu, Junlai; Shen, Liang; Ji, Mo; Guan, Huimei; Zhang, Zhaochong; Zhao, Zhidan
Abstract [1] The Liaodong Peninsula Early Cretaceous extension province (LEP), located in the eastern part of the North China Craton (NCC), was highly extended in early Cretaceous. The Liaonan and the Wanfu metamorphic core complexes (MCCs) are two most important elements in the province. Both are typical Cordilleran‐type core complexes that are composed of a general three‐layered structure but show various differences. Shearing along the Jinzhou detachment fault zone in the Liaonan MCC generated ductile to brittle tectonites, various deformation microstructures, and several types of quartz c‐axis fabrics, implying that the MCC has a complicated progressive exhumation history. However, medium‐temperature microstructures and fabrics are superimposed by low‐temperature features along the Wanfu detachment fault zone suggesting a relatively short and simple exhumation history of the Wanfu MCC. Magmatic zircon U‐Pb geochronological dating reveals that the early Cretaceous extension of the LEP began with the initiation of shearing along the Jinzhou detachment fault zone and exhumation of the Liaonan MCC before ca. 134 Ma. Subsequently, relatively slow cooling and exhumation of the lower plate accompanied a giant magmatic event from 130 Ma to 120 Ma. Exhumation of a new MCC, i.e., the Wanfu MCC, was triggered by progressive extension after ca. 120 Ma. Rapid cooling and exhumation of the metamorphic lower plate of the two MCCs are attributed to coeval detachment faulting along both the Jinzhou and Wanfu faults from 120 Ma to 113 Ma. The extension ended at ca. 107 Ma. These data provide reliable evidence that the two MCCs were exhumed progressively and sequentially during two stages of crustal extension of the LEP. Our results indicates that heterogeneous lithosphere extension and upper‐middle crust/upper mantle detachment, possibly due to the interaction between the Paleo‐Pacific and Eurasian plates, are among the most important processes during the early Cretaceous thinning of the lithosphere. Tectonic extension may have led to the detachment in East Asia, which contributed to the thinning of the lithosphere and the destruction of the NCC. A phase of uniform and consistent WNW‐ESE extension was responsible for the generation of the extensional structures in the eastern Asia continent and the destruction of the NCC.